Spatial Analysis and Spillover Effects on Economic Growth in Central Java - Isna Febriyana; Lilis Siti Badriah (Universitas Negeri Semarang, 2025)
This study investigates the impact of regional spillover effects on economic growth in Central Java’s regencies and cities, focusing on Knowledge Spillover, Industry Spillover, Private Investment Spillover, and Government Expenditure Spillover using a spatial econometrics panel model. The results indicate significant effects on local economic growth; however, direct spillover effects, which are represented by the variable Wx in the Spatial Durbin Model (SDM), were not significant. This may be due to limited resource mobility, varying regional absorption capacities, and temporal dynamics. Direct spillover effects typically involve immediate economic interactions between neighboring regions, but in this study, these effects did not materialize as expected. Conversely, indirect spillover effects, reflected by spatial parameters ρ in the Spatial Autoregressive Model (SAR) and λ in the Spatial Error Model (SEM), highlight the importance of broader spatial dynamics across regions. These effects underscore the significance of interregional linkages rather than direct regional interactions, showing that regional synergies play a crucial role in fostering economic growth. From a policy perspective, the study recommends strengthening interregional cooperation by enhancing mechanisms such as information flow, technology transfer, and investment. Investment in digital infrastructure, the creation of innovation hubs, and cross-regional investment funds can help bridge the development gap and foster sustainable growth. Policies that support labor mobility and skill-building opportunities, especially for marginalized groups and women, are essential to promote equitable and inclusive economic development across regions